Feminismo animalista: a interseção entre discursos e práticas feministas e de libertação animal - Monteiro, Lorena Lúcia Cardoso (2014)
The present work proposes to bring an interpretation of speeches and symbolic aspects involved in the practice of veganism among young feminists. As scholars and other authors of the theme activists, they bring in their discourses and practices political dimensions that relate animal and environmental exploitation, and the consumption of meat and animal clothing, with a patriarchal capitalist system of exploitation that is the same governing domination between people through gender relations. The research comprises a set of methodologies for obtaining data as field research and semi - structured interviews between activists and groups that propose discussion between feminism and animal liberation, which may be located more precisely a feminist anarchist youth culture of young women many places in Brazil; are participants of activist groups, vegan feminist projects, festivals, bands and zines or even autonomous activists.